Annulation of enals with carbamoylpropiolates via NHC-catalyzed enolate pathway: access to functionalized maleimides/iso-maleimides and synthesis of aspergillus FH-X-213 - Viveki, Amol B.; Pol, Mahesh D.; Halder, Priyanka; Sonavane, Sameer R.; Mhaske, Santosh B. (Journal of Organic Chemistry, 2021)
Herein we report the N-heterocyclic carbene (NHC)-catalyzed [3 + 2] annulation of alpha,beta-unsaturated aldehydes with carbamoylpropiolates via an unusual enolate pathway leading to the construction of highly functionalized maleimides or isomaleimides. The electronic effect imposed by the alkyl/aryl group present on the amide nitrogen of carbamoylpropiolates plays a crucial role in the selective formation of these important five-membered heterocyclic building blocks. The developed protocol is mild and tolerates a wide range of substituents on both substrates. The application of this protocol in the synthesis of the antibacterial natural product Aspergillus FH-X-213 has also been demonstrated.